ChemInform Abstract: Regioselective Synthesis of Fused Imidazo[1, 2‐a]pyrimidines via Intramolecular C—N Bond Formation/6‐Endo‐Dig Cycloisomerization. Issue 5 (February 2015) - Kumar, Atul; Kumar, Mukesh; Maurya, Shivam; Khanna, Ranjana S.
Abstract The 3‐component reaction is efficiently catalyzed by the transition metal system.